A study of morbidity pattern among elderly population in urban India - Yadav, Akhilesh; Prasad, Jang Bahadur; Shekher, Chander; Vishvakarma, Minakshi (Journal of Social Health and Diabetes, 2017)
Background: The people in urban area were suffering from different type of morbidities like chronic lung disease, depression, angina, diabetes, etc. Therefore, this study was designed to explore the age pattern of morbidities, level of substance use among elderly, and relationship between substances used and selected morbidities among elderly in urban India.Material and Methods: The information on morbidity was obtained from Study on Global Ageing and Adult Health (SAGE) - 2007. The methods bivariate and multivariate were used for analyzing the data.Results and Discussion: The hypertension, depression, diabetes and disease-related to oral health were highly prevalent in the age group of 50-59 years, while cataracts, asthma, and stroke were more frequent in 60-69 years. In urban India, around every second people in the age group of 50-59 years were smokers whereas people were more alcoholic in 60-69 years. In urban India, Assam was the state where the prevalence of smoking was highest while alcohol consumption was highest in the state of Rajasthan and lowest was in Assam. Moreover, among the elderly people; the third most powerful killer disease (diabetes) was highest in the age the group of 50-59 years. Age, tobacco consumption and improvements in wealth quintile were significant risk factors associated with the presence of morbidities like diabetes, hypertension, and stroke. Asthma and oral health were significant increases along with age.Conclusion: Study confirm that, for reducing these non communicable diseases, there is need to improve old age policy to make proper intension towards the health facility especially among the elderly of middle and higher economic households.
Keywords: Alcohol; elderly; pattern of morbidity; tobacco; urban India